Modelling the molecular composition and nuclear-spin chemistryof collapsing pre-stellar sources. Issue 4 (7th April 2018) - Hily-Blant, P; Faure, A; Rist, C; Pineau des Forêts, G; Flower, D R
ABSTRACT: We study the gravitational collapse of pre-stellar sources and the associated evolution of their chemical composition. We use the University of Grenoble Alpes Astrochemical Network (UGAN ), which includes reactions involving the different nuclear-spin states of H2, H_3^+, and of the hydrides of carbon, nitrogen, oxygen, and sulphur, for reactions involving up to seven protons. In addition, species-to-species rate coefficients are provided for the ortho/para interconversion of the H_3^+ + H2 system and isotopic variants. The composition of the medium is followed from an initial steady state through the early phase of isothermal gravitational collapse. Both the freeze-out of the molecules on to grains and the coagulation of the grains were incorporated in the model. The predicted abundances and column densities of the spin isomers of ammonia and its deuterated forms are compared with those measured recently towards the pre-stellar cores H-MM1, L16293E, and Barnard B1. We find that gas-phase processes alone account satisfactorily for the observations, without recourse to grain-surface reactions. In particular, our model reproduces both the isotopologue abundance ratios and the ortho:para ratios of NH2 D and NHD2 within observational uncertainties. More accurate observations are necessary to distinguish between full scrambling processes – as assumed in our gas-phase network – and direct nucleus- or atom-exchange reactions.